Personalization of Patient–Provider Communication Across the Life Span. Issue 3 (July 2021) - Gormley, Jessica; Koch Fager, Susan
Abstract : People with disabilities are more likely to be hospitalized and use health care services than people without disabilities. They also report negative experiences interacting with health care providers during these encounters, placing them at risk for preventable adverse medical events, poor quality of life, and dependence on others. Fortunately, providers and people with communication disabilities can take steps to improve these interactions by personalizing and implementing communication supports to empower people with communication disabilities to actively participate in these interactions and improve outcomes. The purpose of this article is to describe strategies that health care providers can use to develop and implement personalized communication supports for children and adults with communication disorders during health care interactions. Additional strategies are provided to guide people with disabilities as well as their community/school providers and families to prepare for health care interactions. Case examples are provided to illustrate use of these strategies in acute care, inpatient rehabilitation, and outpatient settings. The use of emerging training tools (e.g., video visual scene displays) and augmentative or alternative communication partner training formats (e.g., just-in-time training) are also presented as future directions to expedite learning and implementation of communication supports in fast-paced and time-limited health care interactions.